2009
DOI: 10.1080/10739680802279394
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Red Cell–Endothelium Interactions

Abstract: Periodic recurrence of painful vaso-occlusive crisis is the defining feature of sickle cell disease. Among multiple pathologies associated with this disease, sickle-red cell-endothelium interaction has been implicated as potential initiating mechanism in vaso-occlusive events. This review focuses on various interrelated mechanisms involved in human sickle red cell adhesion. We discuss in vitro and microcirculatory findings on sickle red cell adhesion, its potential role in vasoocclusion, and the current unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 89 publications
3
167
0
2
Order By: Relevance
“…Though, recent advances in SCD research have revealed a more complex pathophysiology of the disease [2][3][4]. Indeed, it has been demonstrated that inflammation and increased leukocyte-erythrocyte-endothelial interactions are the major potential initiating mechanisms of recurrent occlusion of blood vessels [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Though, recent advances in SCD research have revealed a more complex pathophysiology of the disease [2][3][4]. Indeed, it has been demonstrated that inflammation and increased leukocyte-erythrocyte-endothelial interactions are the major potential initiating mechanisms of recurrent occlusion of blood vessels [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The RBC membrane receptors VLA-4/α4β1 bind to endothelial receptors directly to vascular cell adhesion molecule 1 (VCAM-1) and interacts with subendothelial matrix proteins (BCAM/LU, α4β1 with the laminin and VWF) [37,38]. Red blood cell interactions with the vascular endothelium also lead to the production of oxygen radicals by activating transcription factor NF-κB.…”
Section: Scientific Rationalementioning
confidence: 99%
“…Mechanistically, the interaction between the erythrocytes and the endothelium involves α4β1 integrin, expressed on the erythrocyte surface, and fibronectin, vascular cell adhesion protein 1 (VCAM-1), intracellular adhesion molecule 1 (ICAM-1), and E-selectin, expressed on the endothelial cell surface [19]. Other ligands, including thrombospondin, von Willebrand factor, immunoglobulins, and fibrinogen, also seem to contribute to this adherence [20].…”
Section: Pathophysiologymentioning
confidence: 99%